Electromagnetic Field-Induced Electrotaxis as a Mechanism for Reducing the Neuroanatomical Gap in Cochlear Implants - Delipetar, Boris; Borić, Tina; Žarković, Jelena; Radotić, Viktorija; Bedalov, Ana; Kovačić, Damir (2024 9th International Conference on Smart and Sustainable Technologies, SpliTech 2024, 2024)
Spiral ganglion neurons (SGNs) are the primary auditory neurons in the cochlea that play a key role in connecting the auditory input and the cochlear nucleus. Damage to auditory hair cells without the possibility of regeneration causes irreversible hearing loss. A cochlear implant (CI) is an advanced and effective prosthetic device that converts sound from the environment into an electrical signal that is sent via electrodes directly to the SGNs and thus bypasses damaged auditory hair cells. However, a significant part of users still cannot achieve a satisfactory improvement in hearing quality. One of the causes of this is the neuroanatomical gap (NAG) between electrodes and cells, due to which, in some cases, it is not possible to achieve sufficient contact between electrodes and neurons. This paper explores the mechanism of global electromagnetic field (EMF)-induced electrotaxis as one potential way to reduce NAG. In the experiment, SGNs from P5-P7 rats were cultivated on microchips with customized microtopography and glass coverslips surrounded by a magnetic coil. The effect on the morphological properties of neurons was analyzed from the perspective of further research.
CRIS-Team Scopus Importer:2024-09-06
Keywords: electromagnetic field; electrotaxis; in vitro culturing; micro-pillared substrate; primary auditory neurons